Saturn's Dusty Ionosphere. Issue 3 (22nd March 2019) - Morooka, M. W.; Wahlund, J.‐E.; Hadid, L. Z.; Eriksson, A. I.; Edberg, N. J. T.; Vigren, E.; Andrews, D. J.; Persoon, A. M.; Kurth, W. S.; Gurnett, D. A.; Farrell, W. M.; Waite, J. H.; et al.
Abstract: Measurements of electrons and ions in Saturn's ionosphere down to 1, 500‐km altitudes as well as the ring crossing region above the ionosphere obtained by the Langmuir probe onboard the Cassini spacecraft are presented. Five nearly identical deep ionosphere flybys during the Grand Finale orbits and the Final plunge orbit revealed a rapid increase in the plasma densities and discrepancies between the electrons and ions densities (Ne and Ni ) near the closest approach. The small N e / N i ratio indicates the presence of a dusty plasma, a plasma which charge carrier is dominated by negatively charged heavy particles. Comparison of the Langmuir probe obtained density with the light ion density obtained by the Ion and Neutral Mass Spectrometer confirmed the presence of heavy ions. An unexpected positive floating potential of the probe was also observed when N e / N i  ≪ 1. This suggests that Saturn's ionosphere near the density peak is in a dusty plasma state consisting of negatively and positively charged heavy cluster ions. The electron temperature ( T e ) characteristics in the ionosphere are also investigated and unexpectedly high electron temperature value, up to 5000 K, has been observed below 2, 500‐km altitude in a region where electron‐neutral collisions should be prominent. A well‐defined relationship between T e and N e /N i ratio was found, implying that the electron heating at low altitudes is related to the dusty plasma state of the ionosphere. Plain Language Summary: Cassini Langmuir probe measurements revealed ion densities in excess of the electron densities, indicative of a dusty plasma, in Saturn's ionosphere below 2, 500‐km altitude. Comparison of the Langmuir probe measurements with those of the Ion and Neutral Mass Spectrometer, sensitive to only lighter ions during this period, showed that heavy ions dominate in this region. Positive spacecraft potentials were also found, suggesting that Saturn's ionosphere contains dusty plasma of negatively and positively charged heavy ions. Key Points: In situ measurements of Saturn's ionospheric plasma densities down to 1, 500 km and the ring above the ionosphere is presented Charge imbalance in the ions and electrons, evidence of the negatively charged heavy particles, has been observed below 2, 500 km Observations suggest that Saturn's ionosphere consists of a significant amount of negatively and positively charged heavy ions